Molds on house walls and the effect of their chloroform-extractable metabolites on the respiratory cilia movement of one-day-old chicks in vitro - Piecková, E; Jesenská, Z (Folia microbiologica, 1998)
The ciliostatic activity of the chloroform-extractable endo- and exometabolites of 5 strains of filamentous fungi--Alternaria sp., Aspergillus glaucus group, Aspergillus versicolor, Cladosporium sphoerospermum, Penicillium sp. and Ulocladium sp.--isolated from molded walls of a dwelling--on tracheal cilia from 1-d-old chicks in vitro was evaluated. Endometabolites of Alternaria sp. and A. versicolor and exometabolites of Ulocladium sp. were the most active, these extracts stopped the ciliary movement within 1 d. The results are discussed in relation to the health status of people living in "moldy" dwellings.
Keywords: kur domácí; Cilia; Chloroform; Chickens; Ciliary Motility Disorders; Penicillium; věkové faktory; fungální proteiny; mykózy; trachea; potřeby pro domácnost; Trachea; pneumonie; zvířata; cilie; Cladosporium; Fungal Proteins; Age Factors; Animals; Mycoses; poruchy ciliární motility; chloroform; Pneumonia; Household Articles